Therapeutic effects and mechanisms of Fufang Longdan mixture on metabolic syndrome with psoriasis via miR-29a-5p/IGF-1R axis - Luo, Guangyun; Kong, Xiangyi; Wang, Fang; Wang, Zhiming; Zhang, Zhuo; Cui, Huan; Zhang, Yiwen; Huang, Wen; Yang, Xuesong; Ye, Jianzhou (Frontiers in Pharmacology, 2025)
BackgroundThe occurrence of comorbid metabolic syndrome and psoriasis (MS-P) is owing to the complex interplay between metabolic dysregulation and inflammatory responses. However, current treatments have shown limited efficacy in improving the symptoms of both conditions simultaneously.ObjectiveThis study aimed to investigate the therapeutic efficacy of Fufang Longdan Mixture (FLM) in treating MS-P comorbidity, elucidate its mechanism through the miR-29a-5p/IGF-1R axis and evaluate treatment responses between APOE−/− and C57BL/6 mice.MethodsUPLC-Q-exactive-MS/MS analysis was used to characterise FLM’s chemical composition. Metabolic syndrome was induced in APOE−/− and C57BL/6 mice using a high-fat, high-sugar diet, while psoriasis-like lesions were induced in the mice via the administration of imiquimod. The mice were randomised into control, model, Yinxieling (8 g/kg/d) and FLM (0.5 mL/d) groups. We assessed the treatment efficacy through metabolic parameters, hematoxylin and eosin (H&E) staining and inflammatory cytokine profiling. The direct targeting of IGF-1R by miR-29a-5p was verified via dual-luciferase reporter assays. We analysed the expression patterns and interactions of miR-29a-5p/IGF-1R using RT-qPCR, Western blotting and fluorescence in situ hybridisation.ResultsChemical analysis identified 2,665 compounds in FLM, which were predominantly shikimates and phenylpropanoids (32%), alkaloids (20%) and terpenoids (13%). FLM significantly improved metabolic parameters in MS-P mice, including fasting glucose levels, insulin resistance indices and lipid profiles (p < 0.05), with more pronounced effects observed in the C57BL/6 mice (p < 0.05). FLM demonstrated superior metabolic regulatory effects compared with Yinxieling (p < 0.05). The treatment significantly reduced Psoriasis Area and Severity Index (PASI) scores and inhibited epidermal hyperplasia (p < 0.05). Furthermore, FLM suppressed the pro-inflammatory cytokines, such as GM-CSF, IFN-γ, IL-9 and IL-17, while elevating the anti-inflammatory IL-10 levels (p < 0.05). Dual-luciferase assays confirmed that IGF-1R is a direct target of miR-29a-5p. Mechanistic studies revealed that FLM upregulated miR-29a-5p expression while downregulating IGF-1R (p < 0.05), with evident co-localisation in lesional tissues.ConclusionOur findings demonstrate that FLM effectively ameliorates MS-P comorbidity through modulation of the miR-29a-5p/IGF-1R axis, showing significant therapeutic efficacy across different genetic backgrounds.